MORNING BRIEFING AS AN INTERNAL COMMUNICATION STRATEGY TO IMPROVE EMPLOYEE PRODUCTIVITY AND PERFORMANCE AT PT. AGRODANA FUTURES - Natasya Novela Ananda Putri; Bowo Santoso (RADJA PUBLIKA, 2025)
This study examines the role of Morning briefing as an internal communication strategy to enhance employee productivity and performance at PT. Agrodana Futures. Effective communication serves as a key element in building coordination, task comprehension, and work motivation. The research employed a descriptive qualitative method with a field study approach, including problem identification, literature review, field observation, activity documentation, data collection, and conclusion. The results indicate that regular morning briefings significantly contribute to faster decision-making, stronger team collaboration, and improved work efficiency. These findings affirm that Morning briefing functions as a strategic medium capable of comprehensively boosting employee performance. Therefore, it is recommended that the briefing format be further developed to become more interactive and goal-oriented to maximize its effectiveness.